Escolariedade, salários e empregabilidade: implicações no mercado de empregos do Rio de Janeiro - Seabra, Alexandre Alves de (2002)
The high degree of flexibility has been pointed as one of the outstanding characteristics of the Brazilian job market. Employability is being a frequent discussion issue among the professionals of the human resources area. The Human Capital Theory and the contemporary discussion concerning Employability argue the relationship of the educational practice and of the production practice in a capitalist economical-social structure as a whole. The education consequences in the individuals' life are reflected in several ways, direct and indirectly. Our objective is to evaluate, with statistics methods, and in that universe of consequences, the explanatory events of the relationships between education-wage and education¿job. The main reason of this work is to evaluate the relationship between education, wage and Employability from a structural model perspective, seeking to compare and to contrast two effective theories: the one from the human capital and other from the Employability. To make this analysis, a database of individuals that are working at the formal work market in the Rio de Janeiro Metropolitan Area, had been used. The results showed the education importance on the wage level, as well as, on the Employability factor, whose values and highest taxes correspond to the individuals graduated on the university.